Emerging therapeutics in idiopathic inflammatory myopathy - Shinji Sato (Indian Journal of Rheumatology)
Idiopathic inflammatory myopathies (IIMs) are a heterogeneous group of systemic autoimmune diseases characterized mainly by inflammation of muscle tissue. Although IIM traditionally encompasses polymyositis, dermatomyositis (DM), and inclusion body myositis, the disease concept has been changing in association with progress in diagnostic techniques. Thus, the new disease entities of amyopathic DM (ADM) or clinically ADM and immune-mediated necrotizing myopathy have been recognized recently. Because of the variety of symptoms or low prevalence or difficulty in correct evaluation of muscle strength and function in IIM patients, no standard treatment strategies have been established yet. Currently, glucocorticoids remain the first line of treatment of IIMs, but in addition to these, several other immunosuppressive agents or intravenous immunoglobulin have been used in a variety of different combinations. However, due to clinical heterogeneity of these conditions as well as the number of therapeutic target organs, IIM therapy remains challenging, and refractory cases are especially difficult to treat. In recent years, new therapeutic approaches using biologics or Janus kinase inhibitors, plasma exchange therapy, and other agents have been evaluated for IIMs. However, validation of the efficacy of these new treatment options remains an issue to be resolved. In this article, the author reviews current treatment strategies and new emerging therapies for IIM patients.